WAQF management and its potential role in developing micro and small enterprises in Yemen / Ali Mutahar Mohammed Al-Shami - Mohammed Al-Shami, Ali Mutahar (2019)
Waqf is an important component of the Islamic economic instruments which has contributed to the economic and social development and has helped to eradicate poverty due to scarcity of income and employment. Although Waqf in Yemen had been implemented since the era of Prophet Mohammed (PBUH), it has yet to give impact in contributing to socio-economic development in this present day. Waqf in Yemen, like the rest of the Waqf in the Islamic world, has contributed a significant role in the religious, cultural and social life as well as economic development through the ages. Thus, this thesis aims to shed light on the Waqf management practices in Yemen, the factors affecting Waqf funds and its potential role in developing Micro and Small Enterprises in Yemen. This research used a qualitative and grounded theory approach utilizing thematic analysis. In-depth interviews were conducted with the managers and supervisors of Waqf in Yemen, observations of other countries and codes were used to analyse data. Waqf in Yemen faced problems just like the minor glitches of Waqf in the rest of the Islamic world, but there are serious attempts to restore its historic role by the authorities responsible for Waqf in Yemen. Based on the findings, at present, the practices were contrary to designated purposes of Waqf due to lack of qualified cadre, lack of motivation, prevalence of corruption, incompetent officials, lack of tangible roles, deteriorating economic and political situation in Yemen and misuse of funds. Therefore, this study came out with some recommendations to improve Waqf management in Yemen as well as identifying the significant impact of Waqf implementation in socio-economic development towards Micro and Small Enterprises (MSEs), unemployment, and improving welfare in Yemen.